The Relationship Of Multiple Role Conflict On Work Stress Of State Civil Services (Asn) At The Health Office Of Kaur District - Hesty Novita; Sulisti Afriani; Yesi Indian Ariska (Penerbit Jurnal Indonesia, 2021)
This study aims to find out how the dual role conflict correlation toward work stress on State Civil Apparatus (ASN) in Health Office of Kaur Regency. The data collection method used a questionnaire and documentation. From the total population, a sample of 32 people was taken with a saturated sampling method. The data analysis method used was the quantitative analysis method with Spearman Rank correlation. There is also a significant correlation between multiple role conflicts and work stress of State Civil Apparatus(ASN) in Health Office of Kaur Regency.